[Leonor] - Jasmin Landin::::::photographer::: (2005)
Description supplied by photographer: 'Mi mamá Leonor prepara corundas en el patio de mi casa en Templeton. Nos reunimos con nuestra familia casi cada fin de semana y durante esta reunion celebramos el cumpelaños de mi papá. Las corundas son tamales preparados con chile y queso y se envuelven en hojas. Es una comida típica y tradicional de San Juan Nuevo.' Translation of description: 'My mother Leonor is making corundas in my backyard in Templeton. We have large family gatherings with my dads brothers and our family almost every weekend. We were celebrating my dads birthday. His name is José. Corundas are tamales with chile and/or cheese (no meat) wrapped in leaves. Corundas are a traditional food from San Juan Nuevo.'